1985
DOI: 10.1128/aac.28.2.240
|View full text |Cite
|
Sign up to set email alerts
|

Activity of 9-(1,3-dihydroxy-2-propoxymethyl)guanine compared with that of acyclovir against human, monkey, and rodent cytomegaloviruses

Abstract: The activities of the purine acyclic nucleoside 9-(1,3-dihydroxy-2-propoxymethyl)guanine (DHPG) against two human and five animal strains of cytomegalovirus were compared with those of acyclovir. DHPG was significantly more active than acyclovir against all but one (mouse cytomegalovirus) of the strains tested, with 5Oo% effective doses ranging from 5 to 13 ,uM, as determined by plaque reduction assays in human embryonic lung (MRC-5) and human embryonic tonsil cells. Both DHPG and acyclovir inhibited virus rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(73 citation statements)
references
References 35 publications
3
70
0
Order By: Relevance
“…It has previously been shown that CMV infection increases cellular thymidine kinase activity, and CMV-infected fibroblasts exhibit an increase in dTIP pools (Estes and Huang, 1977;Wachsman et ei., 1995). In fact dramatic increases were seen in all dNTPs upon CMV infection when compared to uninfected cells, in agreement with previous data (Freitas et et., 1985). This increase in thymidine kinase activity may explain the enhanced phosphorylation of AZT in CMV-infected fibroblast cells.…”
Section: Drugssupporting
confidence: 82%
“…It has previously been shown that CMV infection increases cellular thymidine kinase activity, and CMV-infected fibroblasts exhibit an increase in dTIP pools (Estes and Huang, 1977;Wachsman et ei., 1995). In fact dramatic increases were seen in all dNTPs upon CMV infection when compared to uninfected cells, in agreement with previous data (Freitas et et., 1985). This increase in thymidine kinase activity may explain the enhanced phosphorylation of AZT in CMV-infected fibroblast cells.…”
Section: Drugssupporting
confidence: 82%
“…gancyclovir (Field et al, 1983;Freitas et al, 1985). Similarly, varicella-zoster virus (VZV) is a cause of significant morbidity which can be treated with acyclovir (McKendrick et al, 1986), although there is a clear need for more effective chemotherapy.…”
mentioning
confidence: 99%
“…Target plasma trough levels retained during therapeutic drug monitoring ranged from 1 to 2 mg/l. Therefore, the choice of in vitro drug concentrations used for incubation was based on these target levels and previous in vitro studies [14][15][16][17][18]. Table 1.…”
Section: Discussionmentioning
confidence: 99%